1992
DOI: 10.1557/proc-274-85
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Dependence of Domain Structure in Silica-Siloxane Molecular Composites

Abstract: A detailed investigation of the molecular weight dependence of silica growth in in situ filled polydimethylsiloxane/tetraethylorthosilicate (PDMS/TEOS) materials was conducted using small angle neutron scattering (SANS). Composite materials were produced by using TEOS to simultaneously produce the glassy filler phase and to crosslink linear, hydroxyl terminated PDMS of variable molecular weight, M. Correlated domains of glassy filler were produced. The morphology of the in situ filled material showed a definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 6 publications
4
14
0
Order By: Relevance
“…The same was also obtained for the Guinier crossover of sample K at high q. This value has been reported as the distance between metal-oxo domains embedded in the siloxane network [62][63][64], which is in agreement with the results of 29 Si MAS NMR, that indicated the maintenance of the full coordinated Q 4 signal in cross-polarization mode. …”
Section: Small Angle X-ray Scatteringsupporting
confidence: 88%
“…The same was also obtained for the Guinier crossover of sample K at high q. This value has been reported as the distance between metal-oxo domains embedded in the siloxane network [62][63][64], which is in agreement with the results of 29 Si MAS NMR, that indicated the maintenance of the full coordinated Q 4 signal in cross-polarization mode. …”
Section: Small Angle X-ray Scatteringsupporting
confidence: 88%
“…In this case, the phase separation of the hydrolyzed TEOS (which is driven by the extent of the hydrolysis and condensation) occurs in a multicomponent, partially crosslinked system, leading to a complicated interplay of chemical growth and phase separation. 27 Scattering measurements on these composites indicated that particle sizes increased with increase in network mesh size. The simplest interpretation of this constraining effect would be that entropy decreases from the network chains being stretched out as the in situ-generated particles grow larger.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, the relationship between particle or domain size and constraints provided by the polymer environment becomes very important. Some studies have been carried out in this area, 27,31,41 but additional results would be highly desirable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature [43], the peak height is related to the number of coordinated neighbors at a characteristic distance a defined by a = 2π/q. As explained in authors previous works [16,23] this characteristic distance is the distance between metal-oxo domains (main silica primary particles) embedded in the siloxane network [44][45][46]. For both samples this characteristic distance is ca.…”
Section: At Intermediate Values Of Q (Region II Inmentioning
confidence: 56%